Análisis, diseño e implementación de una aplicación web utilizando el framework Django mediante la metodología Das para la administración online de citas médicas para el Hospital Básico la Cigüeña. - Sánchez Liendres, Roxana Elizabeth (2015)
This work titration raised a technological solution to the Basic Hospital Stork located in Machala City, because there was a mess and slow at the time of booking medical appointments and also not had reports the number of appointments held and canceled. user administration, management separation of medical appointments, patient management, administration: therefore an administrable web application available for any device that has Internet access that supports automation of information within each of the processes as developed medical and specialty medical management, reporting and content management of the website. So that to carry out the analysis, design and implementation of this web application, an agile development methodology software called was chosen: DAS (Adaptive Software Development), where adaptation to changing system components is achieved in instead of fighting it. Besides the free software tools they were used: the Python programming language in version 2.7.8, the Django framework that presents flexible and powerful templates separating presentation logic, avoiding redundancy, allowing security and extensibility; for storing data used PostgreSQL in version 9.1, as a database manager robust data which ensures the stability of the system, supporting large amounts of information. Therefore the implementation of the Web Application for Medical Appointments Online Administration achieved better serve the community, providing solutions that help process management within the institution.